Management of The Garment Sewing Training At The Dessy Course And Training Institution (LKP) Semarang - Pamungkas, Triandika Bagus; Suminar, Tri (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2023)
The implementation of training programs requires systematic management to support the achievement of training objectives, but in practice the implementation of management in some institutions is not optimal. Some institutions simply conduct training without structured and systematic management. This study aims to identify and describe training management, which includes 1) planning, 2) implementation and 3) evaluation of training at LKP Dessy. The research design is qualitative and the respondents are executives, trainers, administrators and students. Data collection methods included observing, interviewing, and documentation. Verify data validity by triangulating sources and methods. The data were analyzed using an interactive model that includes data reduction, data presentation, and drawing conclusions. The results showed that LKP Dessy's training management involves 1) Planning includes identifying program managers and support staff, determining: objectives, teaching materials, learning methods, media and tools, evaluation, time and place of training, training instructors, preparing activity plans and schedules, and preparing activity budget plans. 2) Training implementation includes recruiting trainees by distributing brochures and selecting trainees through administrative selection and interviews. The training is conducted using lecture and practical learning methods in accordance with the material presented, and the training is evaluated using daily assessments and competency tests. 3) Evaluate training programs by reviewing skill levels, trainers and program managers, facilities, systems and procedures, and training results. Implementing evaluation at LKP Dessy through discussions between managers, staff and trainers. There is no structured and systematic evaluation in the implementation of evaluation at LKP Dessy